Pathways linking subjective exercise experience to physical activity: mediation by sport enjoyment and interpersonal peace in adolescents - Achmad Rizanul Wahyudi; Muhammad Dzul Fikri; Aprilyan Putra Bimantoro; Afif Rusdiawan; Cemal Özman; Luthfie Lufthansa; Nur Khozanah Ilmah; Farizha Irmawati; Nugroho Susanto (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: Physical activity (PA) among adolescents is connected to subjective exercise experience (SEE) through sport enjoyment (SE) and interpersonal peace (IP), highlighting the significance of relational mediators.